Balance Between Deformation and Seismic Energy Release: The Dec 2018 ‘Double-Dike’ Intrusion at Mt. Etna - Bonaccorso, Alessandro; Giampiccolo, Elisabetta (Frontiers in Earth Science, 2020)
Dikes are the primary mechanisms to transport magma and feed eruptions. Investigations of the surface deformation and seismicity caused by a dike can potentially provide useful information to forecast the expected propagation and associated hazard. On December 24, 2018, a dike intrusion reached the summit of Mt. Etna, feeding an effusive fissure. The intrusion was accompanied by a seismic swarm, with hypocenters beneath the summit craters and eruptive fissure, and by ground deformation. The seismicity continued the following day, with the hypocenters deepening to 3 km b.s.l. due to the propagation of a deeper and thicker dike. This situation generated the fear of feeding a more dangerous eruption in the medium-low flank. Recently it was found an equation that relates the average thickness and dimension of the dike with the expected released mechanical energy and, therefore, to the seismic moment. By using this updated application, it is shown that the observed seismicity could not be accounted for by the first dike. Instead, the cumulative effect of both dikes indicates a total moment from available energy expected that balances the moment recorded by the seismicity. The proposed approach proved very useful in the specific case of Etna volcano eruptions, resulting an effective tool to monitor the state of the intrusion of the magma and, therefore, to predict if a dike has enough energy to continue propagating or to stop.